System Interface Design For CAD/CAM-Simulink Data Exchange System Using MATLAB - Mat Seman, Norhidayah; Jamaludin, Zamberi; Minhat, Mohamad (Springer Nature Singapore Pte. Ltd., 2018)
Integration between advanced control system theory and automation tools and technology brings about advancement in machining technology in tandem with requirement for smart and flexible manufacturing system. The integration takes in the form of seamless and automatic data communication between a CAD/CAM system and the more advanced control systems technology. This paper presents an interface design of a novel CAD/CAM-Simulink Data Exchange System (CS-DES) which links part geometry design using CAD/CAM technology with position controller scheme and algorithm designed in Matlab/Simulink environment. The proposed CS-DES system enhances data automation through formation of the graphical user input reference interface of the machine tools control system using NC manufacturing codes data as the reference input signal. The framework and role of CS-DES are elaborated and described in detail including pseudocodes generation for the CAD drawing graphical data integrated with the controller scheme designed in Simulink. The CS-DES interface was designed using MATLAB graphical user interactive development platform. Functions related to the user interface design are discussed in this paper. Finally, the system interface design of the data exchange system is expected to further enhance versatility of existing control system performance of a machine tool via creation of flexible input reference forms hence improving system accuracy, efficiency and productivity.